EVALUATION OF EFFICIENCY OF PREPARATION OF COMPETITIVE PERSONNEL IN EDUCATION - Khafizovich, Khamidov Obidjon; Siddikovich, Kakhkhorov Otabek (International Journal of Psychosocial Rehabilitation, 2020)
The article highlights the issues of the effectiveness of managerial activities of higher educational institutions, factors and the interaction of the effectiveness of the management process and the management system, indicators of assessing the effectiveness of an educational institution, and the priority of training departments